Pelaksanaan Kegiatan Reses Anggota DPRD Kabupaten Kudus Tahun 2020-2021 Dalam Rangka Penyerapan Aspirasi Masyarakat (Studi Daerah Pemilihan III Jekulo – Dawe) - Zaenudin zaenudin; Aris Suliyono Suliyono (STISIPOL Raja Haji, 2026)
Recess activities are an important instrument for DPRD members in carrying out representative functions and absorbing public aspirations as a basis for regional policy formulation. However, their implementation often encounters obstacles such as low public participation, limited time and budget, and the suboptimal use of recess outcomes in policy planning, as observed in the 2020–2021 recess activities of Kudus Regency DPRD members in Electoral District III Jekulo–Dawe. This study aims to analyze the implementation of these recess activities in absorbing public aspirations and to identify the supporting and inhibiting factors influencing their implementation. This research employs an empirical juridical approach using primary and secondary data, including primary and secondary legal materials. Data were analyzed qualitatively to provide a comprehensive understanding of the issues examined. The results indicate that the implementation of the 2020–2021 recess activities in Electoral District III Jekulo–Dawe has not been optimal. This is reflected in the incomplete accommodation of community aspirations, inconsistencies with the predetermined recess schedule, and the limited integration of recess outcomes into local government work plans and public consultation processes in local regulation formulation. Supporting factors include community participation and the role of political parties, while inhibiting factors consist of budget limitations due to the reallocation of funds for COVID-19 response, limited implementation time, and insufficient socialization prior to the recess activities.